2021
DOI: 10.3389/fphys.2020.616984
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Ultrasound Time-Harmonic Elastography Reveals Softening of the Human Brain Due to Dehydration

Abstract: Hydration influences blood volume, blood viscosity, and water content in soft tissues – variables that determine the biophysical properties of biological tissues including their stiffness. In the brain, the relationship between hydration and stiffness is largely unknown despite the increasing importance of stiffness as a quantitative imaging marker. In this study, we investigated cerebral stiffness (CS) in 12 healthy volunteers using ultrasound time-harmonic elastography (THE) in different hydration states: (i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…There is a substantial body of literature in the fields of non-linear viscoelastic dynamics and poroelasticity indicating that MRE-based brain stiffness is sensitive to changes in ICP 32 , 41 45 . Figure 7 demonstrates the variation and sensitivity of brain stiffness, as measured by MRE and ultrasound elastography, to blood and CSF dynamic parameters such as CPP, CBF, and ICP in subjects with various conditions, including hypothermia (as observed in a mouse study) 46 , hypercapnia 47 , hydration 48 , and intracranial hypertension 49 , as well as in healthy subjects 50 and healthy subjects undergoing the Valsalva maneuver 51 . It is essential to acknowledge that variations in brain stiffness in response to changes in CPP, CBF, and ICP do not consistently exhibit a direct relationship.…”
Section: Resultsmentioning
confidence: 99%
“…There is a substantial body of literature in the fields of non-linear viscoelastic dynamics and poroelasticity indicating that MRE-based brain stiffness is sensitive to changes in ICP 32 , 41 45 . Figure 7 demonstrates the variation and sensitivity of brain stiffness, as measured by MRE and ultrasound elastography, to blood and CSF dynamic parameters such as CPP, CBF, and ICP in subjects with various conditions, including hypothermia (as observed in a mouse study) 46 , hypercapnia 47 , hydration 48 , and intracranial hypertension 49 , as well as in healthy subjects 50 and healthy subjects undergoing the Valsalva maneuver 51 . It is essential to acknowledge that variations in brain stiffness in response to changes in CPP, CBF, and ICP do not consistently exhibit a direct relationship.…”
Section: Resultsmentioning
confidence: 99%
“…15 The combination of hyperglycolysis, alongside additional physiological stressors (in a bout) and hypohydration, may induce a competing substrate demand, which could be further exacerbated by reduced overall blood volume. In addition, it is possible that damage to neurons (eg, diffuse axonal or shear injuries) is enhanced secondary to hypohydration because of altered membrane stability, 31 tissue elasticity, 34 and cerebrospinal fluid production, 35 leaving the brain more vulnerable to cortical damage from trauma. This could, subsequently, lead to prolonged recovery or further exposure to head trauma, which in chronic cases has been associated with later development of neurodegenerative diseases, for example, dementia pugilistica, chronic traumatic encephalopathy, and Alzheimer disease.…”
Section: Discussionmentioning
confidence: 99%
“…A custom-designed patient bed modified with an amplifier and bass shaker unit was used to produce audible soundwaves underneath the participant's head (GAMPT, Merseburg, Germany). The waveform fed into the amplifier consisted of 6 superimposed frequencies of 27, 33, 39, 44, 50, and 56 Hz with identical amplitudes as proposed in Tzschätzsch et al 14 Vibration amplitudes within the brain were adjusted to be larger than 2 μm to ensure that SNR was sufficiently high 24 . Mean vibration amplitudes for all study participants are shown in Supplemental Figure 1, http://links.lww.com/RLI/A643.…”
Section: Methodsmentioning
confidence: 99%
“…The waveform fed into the amplifier consisted of 6 superimposed frequencies of 27, 33, 39, 44, 50, and 56 Hz with identical amplitudes as proposed in Tzschätzsch et al 14 Vibration amplitudes within the brain were adjusted to be larger than 2 μm to ensure that SNR was sufficiently high. 24 Mean vibration amplitudes for all study participants are shown in Supplemental Figure 1, http://links.lww.com/RLI/A643. A clinical ultrasound scanner (SonixMDP; UltraSonix, Scottsdale, AZ) equipped with a convex-array transducer (C5-2/60, 2 MHz) was used for data acquisition.…”
Section: Cerebral Ultrasound Time-harmonic Elastographymentioning
confidence: 99%
See 1 more Smart Citation